2021
DOI: 10.1186/s13023-021-01850-0
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channelopathies and intellectual disability: a systematic review

Abstract: Background Calcium ions are involved in several human cellular processes including corticogenesis, transcription, and synaptogenesis. Nevertheless, the relationship between calcium channelopathies (CCs) and intellectual disability (ID)/global developmental delay (GDD) has been poorly investigated. We hypothesised that CCs play a major role in the development of ID/GDD and that both gain- and loss-of-function variants of calcium channel genes can induce ID/GDD. As a result, we performed a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 302 publications
(381 reference statements)
1
37
0
3
Order By: Relevance
“…Tambasco et al ( 2) also showed that SS was a congenital disorder. Additionally, the neurological channelopathies, which are similar manifestations to SS, have been confirmed as a rare monogenic genetic disease, and a variety of mutant genes, such as SCN, KCNQ, KCNA, CHRNA, GABRB, etc., have been reported (49)(50)(51)(52). This also supports that SS may be a genetic disease.…”
Section: Genetic Factorssupporting
confidence: 68%
“…Tambasco et al ( 2) also showed that SS was a congenital disorder. Additionally, the neurological channelopathies, which are similar manifestations to SS, have been confirmed as a rare monogenic genetic disease, and a variety of mutant genes, such as SCN, KCNQ, KCNA, CHRNA, GABRB, etc., have been reported (49)(50)(51)(52). This also supports that SS may be a genetic disease.…”
Section: Genetic Factorssupporting
confidence: 68%
“…In addition, T-type calcium channels play a central role in either tonic or burst firing of thalamic neurons 84 and T-type calcium blockade can modulate theta/alpha oscillations in the human brain 23 . The contribution of calcium channelopathies is increasingly recognized in intellectual disability syndromes 85 , including known alterations in T-type calcium channels in FXS 29 . This raises speculation for new avenues of therapeutics, including targeting ion channels and non-invasive perturbation channels, to understand mechanisms that promote and maintain suboptimal brain states.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are reports of changes to ion-channel properties and intrinsic properties spanning different neuronal subtypes under several pathophysiological and altered behavioral conditions (Kullmann and Waxman, 2010; Terzic and Perez-Terzic, 2010; Cannon, 2021; Deng and Klyachko, 2021; Franklin and Laubham, 2021; Gripp et al, 2021; Kessi et al, 2021; Mantegazza et al, 2021). Thus, future studies should explore the impact of altered channel properties/densities under different behavioral and pathological conditions on specific ion channels and the physiology of SCN neurons, as well as the impact on transitions and plasticity manifolds associated with them.…”
Section: Discussionmentioning
confidence: 99%